Foundations of the Systemic Reading of Critical and Rhetorical Heritage in the Work of Gaber Asfour - Abdel Rahman, Abdel Dayem (El Omda in Linguistics and Discourse Analysis, 2022)
There are many systematic readings of the Arab critical and rhetorical heritage and differed according to the knowledge backgrounds of their owners, and among these readings is Jaber Asfour’s reading of the critical and rhetorical heritage, this reading was characterized by systematization, briefing and comprehensiveness..From this point of view, this study seeks to investigate the relational levels in the act of reading according to Jaber Asfour, considering that these levels are his starting points in his systematic reading of heritage.